The Implementation of Student Worksheets with Scientific Approach on Reduction Oxidation Reaction Matter to Students’ Cognitive Learning Outcome - Dewiantika Azizah*; Mutiara Dwi Cahyani; Dewi Nurdiyanti (Universitas Syiah Kuala, 2022)
Redox reaction matter which seems to be abstract makes students of X science grade difficult to understand the concept. Therefore, student-centered learning using teaching matter which has analyzed students’ character or as known as scientific-based approach LKPD is necessary. This research aimed to identify the students’ cognitive results after learning redox reaction matter using a scientific-based approach LKPD. The research was done at SMAN 1 Dukupuntang, Cirebon in the 2016-2017 school year using pre-experimental method with one-shot case study research design. The sample was students of X science 2 grade. The data collection was done via a questionnaire. The analysis technique was quantifying the result percentage before and after using LKPD. This research served LKPD data which involved learning activities such as (a) observing, (b) asking, (c) collecting the data, (d) associating, and (e) communicating whichstimulatedstudents to learn redox reaction matter actively. The pretest result showed that the students’ completeness percentage was 66,67% while the protest result using LKPD showed that the percentage increased to be 86,67%. The conclusion was using a scientific-based approach LKPD on redox reaction matter was successful to enhance students’ cognitive learning outcomes and fulfill the minimum completeness criteria (KKM)